Children’s Growth, Nutritional Status, and Its Associated Factors in Karyawangi Village, Indonesia - Alvin Salim; Evi Martha Suryani; Jennifer Simaremare; Jhon Oktavian; Wilson Siahaan; Yomima Herwawan; Lyna Hutapea (Jurnal Cakrawala Ilmiah, 2023)
Stunting as national and global issue needs full attention from parents and healthcare teams. One of the precautions is to monitor children’s growth and nutritional status. The aim of this study is to discover the factors that related to children’s growth and nutritional status to prevent stunting from happening. This is a cross-sectional study with quantitative design and the sample is recruited by purposive sampling technique. Informed consent is obtained from participants and questionnaire from Parongpong Community Health Center is utilized. Thirty-six children become participants with acknowledgement from their parents. Most children are boys, have normal height, also adequate nutrition. Most parents have elementary school education, household income ranged from ±US$64 to ±US$128, owning health insurance, eating at least three times a day, and have balance nutrition in meals. Parental education level becomes the factor of children’s growth and nutritional status in this study. Parental education level is vital to support children’s growth and nutritional status. The other factors may be irrelevant or affected by environment, household ability, and cultural factors in the setting.